Comparing the Outcomes of Surgical and Non-Surgical Approaches in Management of Older Patients with Distal Radius Fracture; a Retrospective Cohort Study - Teimouri, Mehdi; Ghaderi, Milad; Hatami, Saeed (Archives of Academic Emergency Medicine, 2022)
Introduction: Distal radius fractures (DRFs) are the most common orthopedic injuries in emergency department. This study aimed to compare the outcomes of conservative and surgical managements of DRFs in the aged population. Methods: In this retrospective cohort study, ninety patients with unilateral DRFs were treated using either surgical or conservative (casting) approach and the management outcomes as well as complications were compared between the two groups at 3 and 6-month follow-ups. Results: A total of 90 patients over 70 years old were included (45 treated with cast immobilization, and 45 using the surgical method). The mean age (p = 0.56) and gender (p = 0.85) was similar in the two groups. Except for quality of life in both follow-up times, patients treated with surgical methods showed better outcomes in other aspects, including 3-month (p = 0.042) and 6-month (p = 0.022) mean Disability of the Arm Shoulder Hand (DASH) score, 3-month (p = 0.013) and 6-month (p = 0.006) mean range of motion (ROM), and 3-month (p = 0.003) and 6-month (p = 0.033) pain intensity based on Visual Analogue Scale (VAS). A total of 70 (77.77%) adverse events were registered (33 (36.6%) in the casting group and 37 (41.1%) in the surgical group; p = 0.05). The rate of mal-union (p = 0.021) and superficial radial nerve injury (p = 0.026) were significantly lower in the surgical group. Conclusion: The findings suggest that surgical approach for management of DRFs in elder cases has better clinical and functional outcomes than cast immobilization.